Education Financing Management in Improving Elementary School Financial Transparency and Accountability - Julian Sari; Tusia Retno Wulandari; Veronika Windy Sulistiowati; Apri Wahyudi (Civiliza Publishing, Indonesia., 2026)
Educational financing management plays an important role in supporting the quality of education and the effectiveness of school governance. However, financial management in elementary schools still faces challenges related to transparency, accountability, stakeholder involvement, and orderly financial administration. This study aimed to analyze educational financing management in improving transparency and accountability of school financial management at the elementary school level. The research employed a qualitative approach with a descriptive case study design conducted at SD Negeri Sidosari, Natar District, South Lampung Regency, during the second semester of the 2025/2026 academic year. The research subjects consisted of the principal, school treasurer, school committee, and teachers. Data were collected through interviews, observations, documentation studies, and questionnaires, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results showed that financing planning, implementation, transparency, accountability, and the impact of financing management were categorized as very good, with percentages ranging from 83.12% to 86.25%. Financing planning was conducted participatively through stakeholder involvement in preparing the School Activity and Budget Plan (RKAS). Transparency and accountability were implemented through financial reporting, supervision, and orderly financial administration. Therefore, transparent, accountable, and participatory educational financing management contributes to effective school governance and supports the improvement of elementary education quality.